Lt. Charles Gatewood & his Apache wars memoir - Gatewood, Charles B. (University of Nebraska Press, 2005)
Lt. Charles B. Gatewood (1853-1896), an educated Virginian, served in the Sixth U.S. Cavalry as the commander of Indian scouts. Gatewood was largely accepted by the Native peoples with whom he worked because of his efforts to understand their cultures. It was this connection that Gatewood formed with the Indians, and with Geronimo and Naiche in particular, that led to his involvement in the last Apache war and his work for Indian rights. Realizing that he had more experience dealing with Native peoples than other lieutenants serving on the frontier, Gatewood decided to record his experiences. Although he died before he completed his project, the work he left behind remains an important firsthand account of his life as a commander of Apache scouts and as a military commandant of the White Mountain Indian Reservation. Louis Kraft presents Gatewood's previously unpublished account, punctuating it with an introduction, additional text that fills in the gaps in Gatewood's narrative, detailed notes, and an epilogue. Kraft's work offers new background information on Gatewood and discusses the manuscript as a fresh account of how Gatewood viewed the events in which he took part.